The assessment of qualitative olfactory dysfunction in COVID-19 patients: a systematic review of tools and their content validity - Espetvedt, Annelin; Wiig, Siri; Myrnes-Hansen, Kai Victor; Brønnick, Kolbjørn Kallesten (Frontiers in Psychology, 2023)
Background There is a lack of overview of the tools used to assess qualitative olfactory dysfunction, including parosmia and phantosmia, following COVID-19 illness. This could have an impact on the diagnosis and treatment offered to patients. Additionally, the formulations of symptoms are inconsistent and often unclear, and consensus around the wording of questions and responses is needed. Aim of study The aim of this systematic review is to provide an overview of tools used to assess qualitative olfactory dysfunction after COVID-19, in addition to addressing the content validity (i.e. item and response formulations) of these tools. Methods MEDLINE, Web of Science, and EMBASE were searched 5th of August 2022 and updated on the 25th of April 2023 to identify studies that assess qualitative olfactory dysfunction in COVID-19 patients. Primary outcomes were the tool used (i.e. questionnaire or objective test) and item and response formulations. Secondary outcomes included psychometric properties, study design, and demographic variables. Results The assessment of qualitative olfactory dysfunction is characterised by heterogeneity, inconsistency, and lack of validated tools to determine the presence and degree of symptoms. Several tools with overlapping and distinct features were identified in this review, of which some were thorough and detailed, while others were merely assessing the presence of symptoms as a binary measure. Item and response formulations are also inconsistent and often used interchangeably, which may lead to confusion, incorrect diagnoses, and inappropriate methods for solving the problem. Conclusions There is an unmet need for a reliable and validated tool for assessing qualitative olfactory dysfunction, preferably one that also captures quantitative olfactory issues (i.e. loss of smell), to ensure time-effective and specific assessment of the ability to smell. A consensus around the formulation of items and response options is also important to increase the understanding of the problem, both for clinicians, researchers, and the patient, and ultimately to provide the appropriate diagnosis and treatment.